Zastosowanie funkcji logicznych do porządkowania cech jakościowych - Kubus, Mariusz (The Application of the Logical Functions for Nominal Attributes Ordering, 2005)
This paper presents the method of nominal attributes ordering and its application to class description with the use of the logical trees. Minimal logical tree orders attributes according to generality of objects set description. Obtained order is used for description space search. The last variables in order have a little meaning in creating classification rules and often can be omited. Proposed method is compared to well known algorithm AQ11.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 478-484